'Eventually you just get used to it': An interpretative phenomenological analysis of 10–16 year-old girls' experiences of the transition into temporary accommodation after exposure to domestic violence perpetrated by men against their mothers. (April 2015) - Bowyer, Laura; Swanston, Jennifer; Vetere, Arlene
Moving suddenly into temporary accommodation with their mothers is a reality for many children who live with domestic violence. The experience of this transition is under-researched despite being considered a unique event for children alongside that of being exposed to domestic violence involving their mothers. This piece of qualitative research aimed to address the following question: 'How do girls aged 10–16 years old experience the transition into temporary accommodation following exposure to domestic violence'? Five girls aged 10–16 years who had moved into either refuge or 'bed and breakfast' accommodation with their mothers were interviewed. Interviews were analysed using interpretative phenomenological analysis. Three master themes emerged: (1) 'Out of their hands: The transition into a whole new world with loss and change', (2) 'The relentlessness of feeling unsafe and uncertain', (3) 'Coping with the transition: At the mercy of their environment and the actions of others'. All themes show how a lack of agency was experienced by the girls throughout the transition. Findings suggest that the environment of temporary accommodation may inhibit the child's capacity to emotionally process the transition. The role of others was central to either facilitating or constraining coping for the girls throughout this transition.